Composite current collector, lithium ion battery and preparation method based on polyarylene sulfide resin
By using polyaryl sulfide resin and specific preparation methods to prepare the composite fluid, the problems of insufficient high temperature resistance and flame retardancy of the composite fluid in the prior art are solved, and the energy density and production efficiency of lithium-ion batteries are improved. improve.
Patent Information
- Application Number
- CN202410304899.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-18
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-03-18
AI Technical Summary
The high temperature resistance, strength and flame retardancy of the composite liquid collectors of existing lithium-ion batteries are insufficient, and the preparation process is complicated, resulting in low production efficiency and high cost, affecting the energy density and safety of the battery.
Polyaryl sulfide resin is used as the substrate to prepare the composite fluid by specific melt extrusion, stretching and corona treatment methods to form a conductive copper layer to improve the bonding tightness and performance uniformity between the substrate and the copper layer. .
It significantly improves the high temperature resistance, strength and flame retardancy of the composite fluid collection, reduces the total weight and production cost of lithium-ion batteries, and improves the energy density and overall performance of the battery.
Smart Images

Figure CN118380588B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, and in particular to lithium ion batteries based on polyarylene sulfide resins. Background Art
[0002] With the requirement of new energy vehicles for long driving range, improving the energy density of lithium-ion batteries has become a top priority. However, due to the limitations of the performance of the positive and negative electrode materials of lithium-ion batteries, increasing the energy density of lithium-ion batteries by improving the energy density of the positive and negative electrodes has basically reached its limit. Therefore, the current research direction has turned to improving the structure of lithium-ion batteries, among which the use of lightweight materials as the shell and current collector of lithium batteries has become the main breakthrough direction.
[0003] The current collector is one of the most important components used in lithium-ion batteries. It has multiple functions of carrying electrode active materials and collecting output current. Currently, commercial lithium-ion batteries mainly use copper foil and aluminum foil as current collectors for electron transmission. However, both copper foil and aluminum foil have very high density, which will have an adverse effect on the current energy density. In order to reduce this effect, the use of composite current collectors obtained by combining a polymer material matrix with a lower density and a metal coating to replace pure metal foil current collectors has been rapidly developed. This type of composite current collector is usually a sandwich structure with a polymer material as the substrate and copper or aluminum as the load layer. It can take into account the advantages of battery energy density, safety, cost and other aspects, and can greatly reduce the demand for copper or aluminum materials, becoming one of the best solutions to improve battery energy density.
[0004] The polymer materials used as composite current collector substrates in the prior art are mainly PET (polyethylene terephthalate) and PP (polypropylene), etc., and the preparation process is usually as follows: obtain a substrate with a thickness of 4-5 μm, magnetron sputter a metal layer such as a copper layer of 50 nm on both sides of the substrate, and then perform water electroplating on the surface of the copper layer to thicken it to about 1 μm. However, the composite current collector obtained by the above polymer materials and their preparation process has poor high temperature resistance, poor strength, and is flammable. When the lithium ion battery has thermal runaway, the effect of preventing the spread of thermal runaway of the lithium ion battery is not obvious. When the battery cell is stacked and assembled, the stacking temperature can reach 100-120°C, and the substrate of the composite current collector is easy to soften and wrinkle, which seriously affects the quality of the battery cell. At the same time, because the uniformity of the substrate is difficult to control during the preparation process, the magnetron sputtering and evaporation technology is complex, and the bonding strength of the water electroplating layer and the substrate is limited, it has the problems of low production efficiency and high production cost in mass production. Summary of the invention
[0005] In view of the defects of the prior art, the purpose of the present invention is to provide a new composite current collector for lithium ion batteries, a lithium ion battery and a preparation method thereof. The substrate used in the composite current collector is a polyarylene sulfide resin, and the conductive layer is a copper material. A uniform polymer material substrate microfilm and a water electroplated copper layer can be formed during the preparation, and the substrate microfilm is tightly combined with the copper layer without delamination. The obtained composite current collector has good high temperature resistance, strength and flame retardancy, and significantly improves the energy density of the lithium ion battery. It can replace the traditional copper foil current collector or the composite current collector of copper foil and PET, PP. The obtained lithium ion battery is not only light in weight, but also low in cost, stable in quality and high in production efficiency.
[0006] The technical solution of the present invention is as follows:
[0007] A method for preparing a composite current collector based on polyarylene sulfide resin, comprising:
[0008] S1: mixing a polyarylene sulfide resin with a heat dissipation aid and a microporous material to obtain a mixture, and subjecting the mixture to melt extrusion granulation at a temperature range of 280-320° C. to obtain a slice material;
[0009] S2 drying the sliced material at 140° C. for 1-2 hours, and then performing melt extrusion casting, and rolling the obtained cast material into a sheet material;
[0010] S3: longitudinally stretching the thin sheet material at a constant temperature of 200-220°C, and then cooling and shaping it, and temperature-controlled transverse stretching and pulling the cooled and shaped thin sheet material, and then cooling and shaping it to obtain a polyarylene sulfide resin base film; the temperature-controlled transverse stretching and pulling include: transversely stretching the cooled and shaped thin sheet material, and pulling it in the traveling direction while transversely stretching it, and in the process of transverse stretching and pulling, controlling the temperature distribution as follows: in the stretching and widening direction, i.e., in the transverse direction of the thin sheet material, controlling the temperature to decrease symmetrically from the middle to the edge of the thin sheet material according to the stretching distance; in the pulling direction, i.e., in the longitudinal direction of the thin sheet material, controlling the temperature of the middle of the thin sheet material to decrease from the pulling inlet end to the pulling outlet end according to the pulling distance gradient, and the total reduced temperature is that the temperature of the middle of the thin sheet material at the pulling inlet end is 240°C, and the temperature of the middle of the thin sheet material at the pulling outlet end is reduced to 215°C;
[0011] S4: performing a double-sided corona treatment on the polyarylene sulfide resin base film to obtain a pretreated base film;
[0012] S5: The pretreated base film is subjected to double-sided vacuum magnetron sputtering of copper metal to form a copper layer with a single-sided thickness of 50-100 nm, and then the copper layer thickness on each side is increased by water electroplating to form a single-sided total copper layer thickness of 0.5-1.5 μm, thereby obtaining the lithium battery composite current collector based on polyarylene sulfide resin.
[0013] In the above technical scheme of the present invention, the polyarylene sulfide (PAS) resin is a type of high molecular polymer whose main chain structure is alternating sulfur and aromatic structures, such as polyphenylene sulfide (PPS), polyarylene sulfide sulfone (PASS), polyarylene sulfide ketone (PASK), etc., which has excellent high temperature resistance, self-flame retardancy and high strength, and can significantly improve the high temperature resistance, strength and flame retardancy of the obtained composite current collector.
[0014] The above technical scheme of the present invention further modifies the polyarylene sulfide resin by heat dissipation aids and microporous materials to enhance its thermal conductivity, film-forming properties and interface bonding properties, so as to obtain a polyarylene sulfide resin-based film with excellent heat dissipation, uniform thickness and tight interface bonding.
[0015] The above technical scheme of the present invention also takes into account that polyarylene sulfide resin is a crystalline resin with strong rigidity. When subjected to high-temperature transverse stretching, the edges on both sides are easily thinned, which makes it difficult to evenly transmit the tensile force to the middle of the material, resulting in the problem that the material is thick in the middle and thin at both ends. When subjected to low-temperature transverse stretching, stretching defects and brittle fracture problems are likely to occur. Therefore, the present invention adopts a specific temperature-controlled transverse stretching and pulling method, and sets different temperatures in different areas of the material to overcome various problems caused by conventional stretching methods, and obtains a polyarylene sulfide resin base film with more uniform thickness and performance and more significant performance improvement.
[0016] The above technical scheme of the present invention can obtain a polyarylene sulfide base film with uniform thickness through temperature-controlled transverse stretching and longitudinal stretching with a specific temperature distribution, and achieve good heat dissipation of the base film and excellent interface bonding with the copper layer through the heat dissipation aid and microporous material dispersed in the base film.
[0017] Preferably, in order to achieve more precise temperature control, infrared heating is used to control the temperature during the temperature-controlled transverse stretching and traction.
[0018] Preferably, the controlled temperature is symmetrically reduced from the middle to the edge of the sheet material according to the stretching distance, and the total temperature reduction range is that the edge temperature of the sheet material is 5°C lower than the middle temperature.
[0019] Preferably, the polyarylene sulfide resin is selected from polyarylene sulfide resins having a melt index of 50-100 g / 10 min. The polyarylene sulfide resin in this preferred embodiment has excellent strength, toughness and film-forming effect.
[0020] More preferably, the polyarylene sulfide resin is selected from one or more of polyphenylene sulfide resin and polyarylene sulfide sulfone resin having a melt index of 50-100 g / 10 min; more preferably, the polyphenylene sulfide resin is selected from linear polyphenylene sulfide resin.
[0021] Preferably, the heat dissipation aid is selected from one or more of silicon nitride, boron nitride, aluminum oxide, and aluminum nitride. The polyarylene sulfide resin-based film obtained in this preferred manner can have a heat dissipation effect similar to that of pure copper foil when used for lithium-ion battery current collectors.
[0022] Preferably, the microporous material is selected from one or more of microporous alumina, silica aerogel, and diatomaceous earth.
[0023] The addition of the microporous material in the present invention can generate loaded micropores at the interface of the obtained polyarylene sulfide resin base film, which is beneficial to the close combination of the electroplated copper layer and the base film.
[0024] Preferably, the particle size of the heat dissipation aid is 1-5 μm.
[0025] Preferably, the particle size of the microporous material is 1-5 μm.
[0026] Preferably, the polyarylene sulfide resin-based film has a thickness of 5-50 μm.
[0027] Preferably, the mass ratio of the polyarylene sulfide resin, the heat dissipation aid, and the microporous material is 100:0.2-0.5:1-10.
[0028] Preferably, the stretching ratio of the longitudinal stretching in step S3 is 3-3.5 times.
[0029] Preferably, the stretching ratio of the transverse stretching is 3.5-4.5 times.
[0030] Preferably, the stretching rate of the longitudinal stretching is 20-40 m / min.
[0031] Preferably, the stretching rate of the transverse stretching is 45-65 m / min.
[0032] Preferably, the operating voltage of the double-sided corona treatment is 1-3 kV, and the operating frequency is 18-60 kHz.
[0033] This preferred embodiment can produce sufficient roughness on the surface of the base film and expose microporous materials, thereby facilitating the penetration and adhesion of the magnetron sputtering copper layer and enhancing the adhesion between the copper layer and the base film.
[0034] Preferably, the melt extrusion molding in step S1 is achieved by a twin-screw extruder, and the twin-screw extruder includes ten temperature control zones in sequence, and the temperature of each zone is controlled as follows: zone 1 275-285°C, zone 2 315-325°C, zone 3 315-325°C, zone 4 305-315°C, zone 5 305-315°C, zone 6 295-305°C, zone 7 295-305°C, zone 8 285-295°C, zone 9 275-285°C, zone 10 275-285°C.
[0035] Preferably, the melt extrusion casting in step S2 is achieved by a sheet extruder with a T-die, and the sheet extruder includes five temperature control zones in sequence, and the temperatures of each zone and the T-die are controlled as follows: zone 1 275-285°C, zone 2 285-295°C, zone 3 305-315°C, zone 4 315-325°C, zone 5 315-325°C, and the T-die temperature is 320-330°C.
[0036] The present invention further provides a composite current collector based on polyarylene sulfide resin prepared according to the above preparation method.
[0037] The composite current collector has excellent insulation, flame retardancy, high temperature resistance and strength, can effectively prevent thermal runaway of the battery and improve the energy density of the lithium-ion battery. The substrate microfilm is tightly bonded to the copper layer and will not delaminate or split.
[0038] Based on the above composite current collector, the present invention can further obtain a lithium-ion battery containing the above composite current collector, which has high energy density, good strength, high temperature resistance, flame retardancy and thermal conductivity, and the layers of different materials are tightly combined. The overall performance is better than the existing copper foil current collector or the composite current collector of copper foil and polymer materials such as PET and PP.
[0039] The present invention has the following beneficial effects:
[0040] (1) The preparation method of the present invention significantly improves the thickness and performance uniformity of the obtained polyarylene sulfide resin-based film by controlling the specific temperature distribution during biaxial stretching, and fully improves the interface and internal performance of the polyarylene sulfide resin-based film;
[0041] (2) The preparation method of the present invention further optimizes the heat dissipation effect of the obtained polyarylene sulfide resin base film, composite current collector and lithium ion battery by adding a heat dissipation aid to the polyarylene sulfide resin, and can effectively prevent local heat accumulation in the battery;
[0042] (3) The preparation method of the present invention further optimizes the interfacial properties of the resin by adding microporous materials to the polyarylene sulfide resin, so that the microporous materials can be highly adhered to the copper layer during magnetron sputtering of the copper layer and water electroplating of the copper layer, effectively preventing the copper layer from falling off;
[0043] (4) The composite current collector prepared by the present invention can not only reduce the use of copper foil and reduce the cost of lithium-ion batteries, but also has a light weight, which can significantly increase the energy density of lithium-ion batteries, while improving the insulation, flame retardancy and high temperature resistance of the lithium-ion base film, and effectively prevent thermal runaway of the battery, and is easy to promote and apply on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is a temperature distribution diagram in the oven during transverse stretching in step S3 of the embodiment.
[0045] Figure 2 This is a physical picture of the polyarylene sulfide resin base film prepared in Example 2.
[0046] Figure 3 This is a physical picture of the composite current collector prepared in Example 3. DETAILED DESCRIPTION
[0047] The present invention is described in detail below in conjunction with the embodiments and drawings, but it should be understood that the embodiments are only used to exemplify the present invention and do not constitute any limitation on the protection scope of the present invention. All reasonable changes and combinations within the scope of the inventive concept of the present invention fall within the protection scope of the present invention.
[0048] Example 1
[0049] The composite current collector for lithium-ion batteries is prepared by the following steps:
[0050] S1: polyarylene sulfide sulfone with a melt index of 80g / 10min and silicon nitride and silicon dioxide aerogel with a particle size of 1-5μm as heat dissipation aids are mixed in a mass ratio of 100:0.5:1, and the obtained mixture is conveyed to the hopper of a twin-screw extruder for extrusion and slicing; the twin-screw extruder used is a Φ35 extruder with a screw length-diameter ratio of 40:1, and the extrusion temperature control of each zone is: 280°C in zone 1, 320°C in zone 2, 320°C in zone 3, 310°C in zone 4, 310°C in zone 5, 300°C in zone 6, 300°C in zone 7, 290°C in zone 8, 280°C in zone 9, and 280°C in zone 10;
[0051] S2: drying the slices obtained in step S1 at 140°C for 2h, and then feeding them into a sheet extruder, and casting and rolling them through its T-die to form a thin sheet; the extrusion temperature control of each zone of the sheet extruder is: 280°C for zone 1, 290°C for zone 2, 310°C for zone 3, 320°C for zone 4, 320°C for zone 5, and the temperature of the T-die is 325°C;
[0052] S3: The sheet obtained in step S2 is continuously fed into a thermostatic oven, the temperature of the sheet is controlled to be 220°C, and the sheet is longitudinally stretched at a stretching rate of 30 m / min with a stretching ratio of 3, and then cooled and shaped by a cooling roller, and then the cooled and shaped sheet is fed into an oven, and its edge is clamped to perform transverse stretching at a stretching rate of 50 m / min and a stretching ratio of 4, and the transversely stretched sheet is continuously pulled forward in the oven. During the transverse stretching process, refer to the attached Figure 1 , the temperature distribution in the oven is controlled as follows: in the stretching and widening direction, i.e., the transverse direction of the sheet, the temperature is controlled to decrease symmetrically from the middle of the sheet to the edge according to the stretching distance, and the total reduction range is such that the edge of the sheet is 5°C lower than the middle; in the traction direction, i.e., the longitudinal direction of the sheet, the temperature in the middle of the sheet is controlled to decrease gradually from the near end (the oven inlet end) to the far end (the oven outlet end) according to the traction distance, and the total reduction range is such as gradually decreasing from 240°C at the near end to 215°C at the far end; the traction-stretched transversely stretched sheet is shaped and rolled up by a cooling roller to obtain a polyarylene sulfide sulfone-based membrane coil;
[0053] S4: The polyarylene sulfide sulfone base film coil obtained in step S3 is pulled into a corona device, and the two surfaces of the base film are subjected to corona treatment at a voltage of 2 kV and an operating frequency of 30 kHz, so that the surface is roughened and microporous materials are exposed, and the dyne value is greater than 40, so as to facilitate the penetration and adhesion of the magnetron sputtering copper layer, thereby enhancing the adhesion between the copper layer and the base film, and then the pre-treated base film is obtained;
[0054] S5: vacuum magnetron copper sputtering is performed on both sides of the pretreated base film obtained in step S4 to form a 50nm copper layer, and then the copper layer thickness is increased by water electroplating copper to form a copper layer with a total thickness of 1μm on both sides of the base film to obtain a lithium-ion battery composite current collector.
[0055] Example 2
[0056] The composite current collector for lithium-ion batteries is prepared by the following steps:
[0057] S1: Linear polyphenylene sulfide with a melt index of 95g / 10min, silicon nitride as a heat dissipation aid with a particle size of 1-5μm, and acidified water-washed purified diatomaceous earth are mixed in a mass ratio of 100:0.5:2, and the obtained mixture is conveyed to the hopper of a twin-screw extruder for extrusion and slicing; the twin-screw extruder used is a Φ35 extruder with a screw length-diameter ratio of 40:1, and the extrusion temperature control of each zone is: 280°C in zone 1, 320°C in zone 2, 320°C in zone 3, 310°C in zone 4, 310°C in zone 5, 300°C in zone 6, 300°C in zone 7, 290°C in zone 8, 280°C in zone 9, and 280°C in zone 10;
[0058] S2: drying the slices obtained in step S1 at 140°C for 2h, and then feeding them into a sheet extruder, and casting and rolling them through its T-die to form a thin sheet; the extrusion temperature control of each zone of the sheet extruder is: 280°C for zone 1, 290°C for zone 2, 310°C for zone 3, 320°C for zone 4, 320°C for zone 5, and the temperature of the T-die is 325°C;
[0059] S3: The sheet obtained in step S2 is continuously fed into a thermostatic oven, the temperature of the sheet is controlled to be 220°C, and the sheet is longitudinally stretched at a stretching rate of 30 m / min with a stretching ratio of 3, and then cooled and shaped by a cooling roller, and then the cooled and shaped sheet is fed into an oven, and its edge is clamped to perform transverse stretching at a stretching rate of 65 m / min and a stretching ratio of 4.5, and the transversely stretched sheet is continuously pulled forward in the oven. During the transverse stretching process, the temperature distribution in the oven is controlled as shown in the attached figure. Figure 1 As shown in the figure, the pulled transversely stretched sheet is shaped and rolled up by a cooling roller to obtain a polyphenylene sulfide-based film roll, as shown in the figure. Figure 2 As shown;
[0060] S4: The polyphenylene sulfide base film coil obtained in step S3 is pulled into a corona device, and the two surfaces of the base film are subjected to corona treatment at a voltage of 2 kV and an operating frequency of 30 kHz, so that the surface is roughened and microporous materials are exposed, and the dyne value is greater than 40, and then the pretreated base film is obtained;
[0061] S5: vacuum magnetron copper sputtering is performed on both sides of the pretreated base film obtained in step S4 to form a 50nm copper layer, and then the copper layer thickness is increased by water electroplating copper to form a copper layer with a total thickness of 1μm on both sides of the base film to obtain a lithium-ion battery composite current collector.
[0062] Example 3
[0063] The composite current collector for lithium-ion batteries is prepared by the following steps:
[0064] S1: polyarylene sulfide sulfone with a melt index of 80g / 10min and aluminum nitride and silicon dioxide aerogel with a particle size of 1-5μm as heat dissipation aids are mixed in a mass ratio of 100:0.5:1, and the obtained mixture is conveyed to the hopper of a twin-screw extruder for extrusion and slicing; the twin-screw extruder used is a Φ35 extruder with a screw length-diameter ratio of 40:1, and the extrusion temperature control of each zone is: 280°C in zone 1, 320°C in zone 2, 320°C in zone 3, 310°C in zone 4, 310°C in zone 5, 300°C in zone 6, 300°C in zone 7, 290°C in zone 8, 280°C in zone 9, and 280°C in zone 10;
[0065] S2: drying the slices obtained in step S1 at 140°C for 2h, and then feeding them into a sheet extruder, and casting and rolling them through its T-die to form a thin sheet; the extrusion temperature control of each zone of the sheet extruder is: 280°C for zone 1, 290°C for zone 2, 310°C for zone 3, 320°C for zone 4, 320°C for zone 5, and the temperature of the T-die is 325°C;
[0066] S3: The sheet obtained in step S2 is continuously fed into a thermostatic oven, the temperature of the sheet is controlled to be 220°C, and the sheet is longitudinally stretched at a stretching rate of 30 m / min with a stretching ratio of 3, and then cooled and shaped by a cooling roller, and then the cooled and shaped sheet is fed into an oven, and its edge is clamped to perform transverse stretching at a stretching rate of 45 m / min and a stretching ratio of 3.5, and the transversely stretched sheet is continuously pulled forward in the oven. During the transverse stretching process, the temperature distribution in the oven is controlled as shown in the attached figure. Figure 1 As shown, the pulled transversely stretched sheet is shaped and rolled up by a cooling roller to obtain a polyarylene sulfide sulfone based membrane roll;
[0067] S4: The polyarylene sulfide sulfone base film coil obtained in step S3 is pulled into a corona device, and the two surfaces of the base film are corona treated at a voltage of 2 kV and an operating frequency of 50 kHz, so that the surface is roughened and microporous materials are exposed, and the dyne value is greater than 40, and then the pretreated base film is obtained;
[0068] S5: vacuum magnetron copper sputtering is performed on both sides of the pretreated base film obtained in step S4 to form a 50 nm copper layer, and then the copper layer thickness is increased by water electroplating copper to form a copper layer with a total thickness of 1 μm on both sides of the base film to obtain a lithium ion battery composite current collector, as shown in the attached Figure 3 shown.
[0069] Example 4
[0070] The composite current collector for lithium-ion batteries is prepared by the following steps:
[0071] S1: polyarylene sulfide sulfone with a melt index of 80g / 10min, silicon nitride as a heat dissipation aid with a particle size of 1-5μm and microporous alumina powder are mixed in a mass ratio of 100:0.5:3, and the obtained mixture is conveyed to the hopper of a twin-screw extruder for extrusion and slicing; the twin-screw extruder used is a Φ35 extruder with a screw length-diameter ratio of 40:1, and the extrusion temperature control of each zone is: 280°C in zone 1, 320°C in zone 2, 320°C in zone 3, 310°C in zone 4, 310°C in zone 5, 300°C in zone 6, 300°C in zone 7, 290°C in zone 8, 280°C in zone 9, and 280°C in zone 10;
[0072] S2: drying the slices obtained in step S1 at 140°C for 2h, and then feeding them into a sheet extruder, and casting and rolling them through its T-die to form a thin sheet; the extrusion temperature control of each zone of the sheet extruder is: 280°C for zone 1, 290°C for zone 2, 310°C for zone 3, 320°C for zone 4, 320°C for zone 5, and the temperature of the T-die is 325°C;
[0073] S3: The sheet obtained in step S2 is continuously fed into a thermostatic oven, the temperature of the sheet is controlled to be 220°C, and the sheet is longitudinally stretched at a stretching rate of 30 m / min with a stretching ratio of 3, and then cooled and shaped by a cooling roller, and then the cooled and shaped sheet is fed into an oven, and its edge is clamped to perform transverse stretching at a stretching rate of 45 m / min and a stretching ratio of 4, and the transversely stretched sheet is continuously pulled forward in the oven. During the transverse stretching process, the temperature distribution in the oven is controlled as shown in the attached figure. Figure 1 As shown, the pulled transversely stretched sheet is shaped and rolled up by a cooling roller to obtain a polyarylene sulfide sulfone based membrane roll;
[0074] S4: The polyarylene sulfide sulfone base film coil obtained in step S3 is pulled into a corona device, and the two surfaces of the base film are corona treated at a voltage of 2 kV and an operating frequency of 30 kHz, so that the surface is roughened and microporous materials are exposed, and the dyne value is greater than 40, and then the pretreated base film is obtained;
[0075] S5: vacuum magnetron copper sputtering is performed on both sides of the pretreated base film obtained in step S4 to form a 50nm copper layer, and then the copper layer thickness is increased by water electroplating copper to form a copper layer with a total thickness of 1μm on both sides of the base film to obtain a lithium-ion battery composite current collector.
[0076] Comparative Example 1
[0077] The comparative current collector was prepared by the following steps:
[0078] S1: polyarylene sulfide sulfone with a melt index of 80g / 10min and silicon nitride and silicon dioxide aerogel with a particle size of 1-5μm as heat dissipation aids are mixed in a mass ratio of 100:0.5:1, and the obtained mixture is conveyed to the hopper of a twin-screw extruder for extrusion and slicing; the twin-screw extruder used is a Φ35 extruder with a screw length-diameter ratio of 40:1, and the extrusion temperature control of each zone is: 280°C in zone 1, 320°C in zone 2, 320°C in zone 3, 310°C in zone 4, 310°C in zone 5, 300°C in zone 6, 300°C in zone 7, 290°C in zone 8, 280°C in zone 9, and 280°C in zone 10;
[0079] S2: drying the slices obtained in step S1 at 140°C for 2h, and then feeding them into a sheet extruder, and casting and rolling them through its T-die to form a thin sheet; the extrusion temperature control of each zone of the sheet extruder is: 280°C for zone 1, 290°C for zone 2, 310°C for zone 3, 320°C for zone 4, 320°C for zone 5, and the temperature of the T-die is 325°C;
[0080] S3: continuously feeding the thin sheet obtained in step S2 into a constant temperature box, controlling the temperature of the thin sheet to 220° C., and longitudinally stretching it at a stretching rate of 30 m / min with a stretching ratio of 3, then cooling and shaping it with a cooling roller, and then feeding the cooled and shaped sheet into an oven, controlling the temperature in the oven to 230° C., and performing constant temperature transverse stretching on the sheet, with a stretching rate of 50 m / min and a stretching ratio of 4, and continuously pulling the transversely stretched sheet forward in the oven, shaping the transversely stretched sheet with a cooling roller, and winding it up to obtain a polyarylene sulfide sulfone-based membrane coil;
[0081] S4: The polyarylene sulfide sulfone base film coil obtained in step S3 is pulled into a corona device, and the two surfaces of the base film are corona treated at a voltage of 2 kV and an operating frequency of 30 kHz, so that the surface is roughened and microporous materials are exposed, and the dyne value is greater than 40, and then the pretreated base film is obtained;
[0082] S5: vacuum magnetron copper sputtering is performed on both sides of the pretreated base film obtained in step S4 to form a 50 nm copper layer, and then the copper layer thickness is increased by water electroplating copper to form a copper layer with a total thickness of 1 μm on both sides of the base film to obtain a comparative current collector.
[0083] Comparative Example 2
[0084] The comparative current collector was prepared by the following steps:
[0085] S1: polyarylene sulfide sulfone with a melt index of 80g / 10min and silicon nitride as a heat dissipation aid with a particle size of 1-5μm are mixed in a mass ratio of 100:0.5, and the obtained mixture is conveyed to the hopper of a twin-screw extruder for extrusion and slicing; the twin-screw extruder used is a Φ35 extruder with a screw length-diameter ratio of 40:1, and the extrusion temperature control of each zone is: 280°C in zone 1, 320°C in zone 2, 320°C in zone 3, 310°C in zone 4, 310°C in zone 5, 300°C in zone 6, 300°C in zone 7, 290°C in zone 8, 280°C in zone 9, and 280°C in zone 10;
[0086] S2: drying the slices obtained in step S1 at 140°C for 2h, and then feeding them into a sheet extruder, and casting and rolling them through its T-die to form a thin sheet; the extrusion temperature control of each zone of the sheet extruder is: 280°C for zone 1, 290°C for zone 2, 310°C for zone 3, 320°C for zone 4, 320°C for zone 5, and the temperature of the T-die is 325°C;
[0087] S3: The sheet obtained in step S2 is continuously fed into a thermostatic oven, the temperature of the sheet is controlled to be 220°C, and the sheet is longitudinally stretched at a stretching rate of 30 m / min with a stretching ratio of 3, then cooled and shaped by a cooling roller, and then the cooled and shaped sheet is fed into an oven, and its edge is clamped to perform transverse stretching at a stretching rate of 50 m / min and a stretching ratio of 4, and the transversely stretched sheet is continuously pulled forward in the oven. During the transverse stretching process, the temperature distribution in the oven is controlled as shown in the attached figure. Figure 1 As shown, the pulled transversely stretched sheet is shaped and rolled up by a cooling roller to obtain a polyarylene sulfide sulfone based membrane roll;
[0088] S4: The polyarylene sulfide sulfone base film coil obtained in step S3 is pulled into a corona device, and the two surfaces of the base film are corona treated at a voltage of 2 kV and an operating frequency of 30 kHz, so that the surface is roughened and microporous materials are exposed, and the dyne value is greater than 40, and then the pretreated base film is obtained;
[0089] S5: vacuum magnetron copper sputtering is performed on both sides of the pretreated base film obtained in step S4 to form a 50 nm copper layer, and then the copper layer thickness is increased by water electroplating copper to form a copper layer with a total thickness of 1 μm on both sides of the base film to obtain a comparative current collector.
[0090] Comparative Example 3
[0091] The comparative current collector was prepared by the following steps:
[0092] S1: polyarylene sulfide sulfone with a melt index of 80g / 10min and silicon nitride and silicon dioxide aerogel with a particle size of 1-5μm as heat dissipation aids are mixed in a mass ratio of 100:0.5:1, and the obtained mixture is conveyed to the hopper of a twin-screw extruder for extrusion and slicing; the twin-screw extruder used is a Φ35 extruder with a screw length-diameter ratio of 40:1, and the extrusion temperature control of each zone is: 280°C in zone 1, 320°C in zone 2, 320°C in zone 3, 310°C in zone 4, 310°C in zone 5, 300°C in zone 6, 300°C in zone 7, 290°C in zone 8, 280°C in zone 9, and 280°C in zone 10;
[0093] S2: drying the slices obtained in step S1 at 140°C for 2h, and then feeding them into a sheet extruder, and casting and rolling them through its T-die to form a thin sheet; the extrusion temperature control of each zone of the sheet extruder is: 280°C for zone 1, 290°C for zone 2, 310°C for zone 3, 320°C for zone 4, 320°C for zone 5, and the temperature of the T-die is 325°C;
[0094] S3: The sheet obtained in step S2 is continuously fed into a thermostatic oven, the temperature of the sheet is controlled to be 220°C, and the sheet is longitudinally stretched at a stretching rate of 30 m / min with a stretching ratio of 3, then cooled and shaped by a cooling roller, and then the cooled and shaped sheet is fed into an oven, and its edge is clamped to perform transverse stretching at a stretching rate of 50 m / min and a stretching ratio of 4, and the transversely stretched sheet is continuously pulled forward in the oven. During the transverse stretching process, the temperature distribution in the oven is controlled as shown in the attached figure. Figure 1 As shown, the pulled transversely stretched sheet is shaped and rolled up by a cooling roller to obtain a polyarylene sulfide sulfone based membrane roll;
[0095] S4: vacuum magnetron copper sputtering is performed on both sides of the polyarylene sulfide sulfone base film roll obtained in step S3 to form a 50 nm copper layer, and then the copper layer thickness is increased by water electroplating copper to form a copper layer with a total thickness of 1 μm on both sides of the base film to obtain a comparative current collector.
[0096] Further, the above Examples 1-4 and Comparative Examples 1-3 were tested as follows:
[0097] (1) The base films obtained in Examples 1-4 and Comparative Examples 1-3 were tested for thickness uniformity. Five points evenly spaced in the lateral direction of each base film were selected for thickness testing. The test results are shown in Table 1 below:
[0098] Table 1 Base film thickness uniformity test results
[0099]
[0100] It can be seen from the above thickness test results that the base film obtained by the technical solution of the present invention has a uniform thickness, and the thickness error range is within 0.5 μm; while the conventional temperature-controlled transverse stretching method adopted in Comparative Example 1 will cause the thickness error of the obtained base film to reach 3.5 μm. Obviously, the present invention achieves a highly uniform distribution of the thickness of the polyarylene sulfide resin base film by controlling the temperature distribution of different regions during transverse stretching.
[0101] (2) The anti-delamination performance of the copper layer in the lithium ion battery composite current collector obtained in Examples 1-4 and the comparative current collector obtained in Comparative Examples 1-3 was analyzed by the tape method according to the standard ASTM D3359. The analysis was performed by a cross-cutting method, which was scratched to the base film. A brush was then used to remove the peeled powder and the tape was adhered. The tape was then torn off to observe the peeling of the copper layer. The performance judgment criteria based on the peeling condition were as follows:
[0102] 5B-The cutting area is smooth without peeling powder;
[0103] 4B-There is a small amount of peeling at the intersection, less than 5% of the area;
[0104] 3B-There is a small amount of peeling at the secant and intersection, and the peeling area is 5-15%;
[0105] 2B-Some grids are completely detached, with a detached area of 15-35%;
[0106] 1B- Extensive peeling, peeling area 35-65%.
[0107] The analysis results are shown in Table 2 below:
[0108] Table 2 Analysis results of the anti-delamination performance of the copper layer
[0109] sample Copper layer delamination Determination level Example 1 The cutting area is smooth without peeling powder 5B Example 2 The cutting area is smooth without peeling powder 5B Example 3 The cutting area is smooth without peeling powder 5B Example 4 The cutting area is smooth without peeling powder 5B Comparative Example 1 The cutting area is smooth without peeling powder 5B Comparative Example 2 There is a small amount of peeling at the secant and intersection, and the peeling area is 8% 3B Comparative Example 3 There is a small amount of peeling at the intersection, less than 5% of the area 4B
[0110] It can be seen from the above test results that in the preparation process of Comparative Example 2, no microporous inorganic material was used, which affected the adhesion of the copper layer and caused it to peel off obviously. In the preparation process of Comparative Example 3, although microporous materials were used, no corona treatment was performed, and the copper layer also peeled off. Compared with Comparative Examples 2 and 3, the present invention uses microporous materials and assists with corona treatment, which makes the base film interface rough and increases micropores, significantly enhancing the adhesion of the copper layer.
[0111] The above embodiments are only preferred implementations of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a composite current collector based on polyarylene sulfide resin, characterized in that: It includes: S1. Mixing a polyarylene sulfide resin with a heat dissipation aid and a microporous material to obtain a mixture, and melt-extruding and granulating the mixture at a temperature range of 280-320° C. to obtain a slice material; S2 drying the sliced material at 140° C. for 1-2 hours, and then performing melt extrusion casting, and rolling the obtained cast material into a sheet material; S3: longitudinally stretching the thin sheet material at a constant temperature of 200-220°C, and then cooling and shaping it, and temperature-controlled transverse stretching and pulling the cooled and shaped thin sheet material, and then cooling and shaping it to obtain a polyarylene sulfide resin base film; the temperature-controlled transverse stretching and pulling include: transversely stretching the cooled and shaped thin sheet material, and pulling it in the traveling direction while transversely stretching it, and in the process of transverse stretching and pulling, controlling the temperature distribution as follows: in the stretching and widening direction, i.e., in the transverse direction of the thin sheet material, controlling the temperature to decrease symmetrically from the middle to the edge of the thin sheet material according to the stretching distance; in the pulling direction, i.e., in the longitudinal direction of the thin sheet material, controlling the temperature of the middle of the thin sheet material to decrease from the pulling inlet end to the pulling outlet end according to the pulling distance gradient, and the total reduced temperature is that the temperature of the middle of the thin sheet material at the pulling inlet end is 240°C, and the temperature of the middle of the thin sheet material at the pulling outlet end is reduced to 215°C; S4: performing a double-sided corona treatment on the polyarylene sulfide resin base film to obtain a pretreated base film; S5: performing vacuum magnetron sputtering on both sides of the pretreated base film to form a copper layer with a single-side thickness of 50-100 nm, and then increasing the thickness of the copper layer on each side by water electroplating to form a single-side total thickness of 0.5-1.5 μm copper layer, to obtain the polyarylene sulfide resin-based lithium battery composite current collector; Among them, the heat dissipation aid is selected from one or more of silicon nitride, boron nitride, and aluminum nitride; the microporous material is selected from one or more of microporous alumina, silica aerogel, and diatomaceous earth; the controlled temperature decreases symmetrically from the middle to the edge of the thin sheet material according to the stretching distance, and the total temperature reduction range is that the edge temperature of the thin sheet material is 5°C lower than the middle temperature.
2. The preparation method according to claim 1, characterized in that: in, The polyarylene sulfide resin is selected from polyarylene sulfide resins having a melt index of 50-100 g / 10 min.
3. The preparation method according to claim 2, characterized in that: The polyarylene sulfide resin is selected from one or more of polyphenylene sulfide resin and polyarylene sulfide sulfone resin having a melt index of 50-100 g / 10 min.
4. The preparation method according to claim 3, characterized in that: The polyphenylene sulfide resin is selected from linear polyphenylene sulfide resins.
5. The preparation method according to claim 1, characterized in that: in, The particle size of the heat dissipation aid is 1-5 μm; and / or the particle size of the microporous material is 1-5 μm; and / or the thickness of the polyarylene sulfide resin-based film is 5-50 μm.
6. The preparation method according to claim 1, characterized in that: in, The mass ratio of the polyarylene sulfide resin, the heat dissipation aid, and the microporous material in step S1 is 100:0.2-0.5:1-10; and / or, the stretching ratio of the longitudinal stretching in step S3 is 3-3.5 times, and / or the stretching ratio of the transverse stretching is 3.5-4.5 times, and / or, the stretching rate of the longitudinal stretching is 20-40m / min, and / or, the stretching rate of the transverse stretching is 45-65m / min; and / or, the working voltage of the double-sided corona treatment in step S4 is 1-3kV, and the working frequency is 18-60kHz.
7. The preparation method according to claim 1, characterized in that: The melt extrusion granulation in step S1 is achieved by a twin-screw extruder, which includes ten temperature control zones in sequence, and the temperature of each zone is controlled as follows: zone 1 275-285°C, zone 2 315-325°C, zone 3 315-325°C, zone 4 305-315°C, zone 5 305-315°C, zone 6 295-305°C, zone 7 295-305°C, zone 8 285-295°C, zone 9 275-285°C, and zone 10 275-285°C.
8. The preparation method according to claim 1, characterized in that: The melt extrusion casting in step S2 is achieved by a sheet extruder with a T-die, and the sheet extruder includes five temperature control zones in sequence, and the temperatures of each zone and the T-die are controlled as follows: zone 1 275-285°C, zone 2 285-295°C, zone 3 305-315°C, zone 4 315-325°C, zone 5 315-325°C, and the T-die temperature is 320-330°C. 9 . The composite current collector based on polyarylene sulfide resin prepared by the preparation method according to claim 1 . 10 . A lithium ion battery comprising the composite current collector based on the polyarylene sulfide resin according to claim 9 .